Kariki Jogijara i wedyjska tradycja wznoszenia ołtarzy ofiarnych w Kerali - Nowicka, Olga (Studia Azjatystyczne, 2017)
The article concerns a hitherto little known Sanskrit text called Karikas of Yogiyar a medieval commentary to Baudhayanaśulvasutra (ca. 5th century BC). The text in question deals with the construction of the Vedic altars specific to the Keralan sacrificial tradition. It is attributed to the ascetic Yogiyar from the village Taikkat Mana (Edappal), who probably lived around 16th or 17th century. Karikas of Yogiyar are presumably the only known independent śulvasutra commentary in Sanskrit of the post-Vedic period.